Improving students’ learning achievement through group counseling of Islamic Cultural History - Su lastri (Prodi PGMI IAIN Salatiga, 2017)
Learning achievement is the change of cognitive, affective, and psychomotor aspect as the effect of learning process which is measured through assessment, as the treatment to assess how far the material has been mastered by learners after getting learning experiences. This research was aimed to know the improvement of students’ learning achievements that have learning difficulty in group counseling of Islamic Cultural History subject. It was a classroom action research which was conducted in two cycles at the eighth grade of MTs Al Islam Pabelan Bringin in the second semester of 2016 academic year. The instruments which were used in this research were: a) syllabus; b) lesson plan; c) formative test. This research resulted that The research resulted that, the students’ learning outcome in learning the Islamic Cultural History at the eightth grade of MTs Al Islam Bringin in the pre cycle reached 25,80%, then in the first cycle it reached 58,06% so there was an improvement about 19.35%. learning reflection in the first cycle showed an improvement in teacher role as well as the percentage of learning outcome. However, it had not been maximal yet. While in the second cycle, it tend to describe the activity in group, that students were more proactive. As the result, the students’ learning outcome reached 77.41%. although it has not reached 100% yet it can be concluded that learners had passed the passing grade because it had reached over 75%.Keywords: learning ability, group counceling, learning achievement AbstrakHasil belajar merupakan semua perubahan kognitif, afektif dan psikomotorik sebagai akibat dari proses belajar mengajar yang diukur melalui kegiatan penilaian, sebagai suatu tindakan untuk menilai sejauh mana materi yang diberikan dikuasai peserta didik, setelah menerima pengalaman belajarnya. Penelitian ini bertujuan untuk mengetahui peningkatan hasil belajar anak yang mengalami kesulitan belajar melalui kegiatan bimbingan belajar pada materi pembelajaran Sejarah Kebudayaan Islam. Penelitian ini adalah penelitian tindakan kelas yang dilakukan di kelas VIII MTs Al Islam Pabelan Bringin pada semester II tahun 2016 yang dilaksanakan dalam 2 siklus. Instrumen yang digunakan dalam penelitian ini terdiri dari: a) silabus; b) rencana pembelajaran; c) tes fomatif. Hasil penelitian yang dilakukan, bahwa kemampuan peserta didik dalam pelajaran Sejarah Kebudayaan Islam di kelas VIII MTs Al Islam Bringin pada pra siklus ketuntasannya mencapai 25,80%, kemudian siklus I mencapai 58,06% sehingga mengalami peningkatan sebesar 32,26%. Penerapan bimbingan belajar kelompok dapat meningkatkan kemampuan peserta didik dalam mata pelajaran SKI, terlihat dari siklus I mencapai 58,06% dan pada siklus II mencapai 77,41% sehingga mengalami peningkatan 19,35%. Perbaikan pembelajaran pada siklus I menunjukkan adanya peningkatan baik peran guru maupun persentase ketuntasan belajar. Namun demikian hasil belajar peserta didik belum maksimal. Sementara itu pembelajaran siklus II menjelaskan kegiatan dalam kelompok, peserta didik tampak lebih proaktif. Hasilnya ketuntasan belajar peserta didik mencapai 77,41% meskipun belum dapat mencapai 100%, namun dapat dikatakan bahwa peserta didik telah mencapai ketuntasan belajar sebab telah memenuhi standar ketuntasan belajar 75%. Kata kunci: kemampuan belajar, bimbingan belajar, hasil belajar